An approximate algorithm for the two-dimensional air cargo revenue management problem - Huang, Kuancheng; Chang, Ko-chen (Transportation research. Part E, Logistics and transportation review, 2010)
For the air cargo revenue management problem, this study developed a solution algorithm based on approximating the expected revenue function in the dynamic programming (DP) model while taking into account the stochastic volume and weight of shipments. In order to alleviate the computational load, the approximation was achieved by computing only a limited number of points in the DP state space. In the simulation experiment, the developed algorithm was compared with a recent heuristic algorithm based on de-coupling the relationship between weight and volume. It was found that the approach of this study can generate higher revenue than the de-coupling control for most of the cases.